APPLICATION OF TRANSPORT MODELING IN URBAN PLANNING USING THE EXAMPLE OF VINNYTSIA - PERLOV, VIKTOR; KYRYTSYA, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The issues of using transportation modeling for decision-making in urban planning are discussed using the example of Vinnytsia. Macro-simulation allows for analyzing overall traffic flow without reproducing the movement of individual vehicles in detail. It enables a quick evaluation of different scenarios for the development of the transportation network and determining the effectiveness of road traffic management strategies. The transportation model of the city enables analyzing the load on the road network in the current state and predicting this parameter for scenarios of implementing new infrastructure projects. Examples of load maps for the road network of Vinnytsia and an individual transport hub are shown from the transportation model of the city.Micro-modeling is the process of creating a mathematical model for a detailed analysis of vehicle movement in small areas (intersections, street sections, enterprise areas, etc.). An example of micro-modeling results for one intersection is presented. The application of micro-modeling in evaluating changes to the transportation network is an effective tool that allows municipalities to avoid inefficient use of funds and transportation mistakes that worsen traffic conditions. A list of tasks for micro and macro-modeling is analyzed. The main advantages and disadvantages of modeling and the risks that may arise from its use are described. The importance of the transportation model of the city is shown in both strategic and tactical approaches.
Keywords: transport model; macromodeling; micromodeling; transport planning